The Effect of a Peer-Group Support Intervention Program on the Tensions of Mothers with Premature Neonates Admitted to the Intensive Care Units in Babol, Iran - Taheri, Maryam; Nikfarid, Lida; Shirinabadi Farahani, Azam; Shakeri, Nezhat (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Admission of premature neonates to the neonates intensive care unit (NICU) encounters mothers with tension, which affects mother-neonate relationship. The current study aimed at investigating the impact of peer support on the tension of mothers of premature infants admitted to NICUs of the selected hospitals in Babol, Iran. Methods: The current before-and-after, two-group, quasi-experimental study, was conducted on 40 mothers with neonates who recently admitted to NICU in order to participate in peer-group support program. The amount of tension in the study participants was measured, before and after the intervention and the results were compared with those of the control group, using parental tension scale: NICU. Results: The average tension in the intervention and control groups before and after the intervention, and comparison of measures between the groups were125.2 (23.10), 135.2 (19.88), 33.35 (8.19), and 49.40 (18.63), respectively. There was a significant difference between the mean score of tension before and after the intervention in both the study groups. There was no significant difference in tension scores between the two groups, before and after the intervention. Conclusions: Hospitals should meet the requirements of